TEACHERS’ SMK AND PCK OF MATHEMATICS AND SCIENCE AFFECT TEACHING IN GABORONE PRESCHOOLS - BOSE, KABITA; Seetso, Grace (Advances in Social Sciences Research Journal, 2019)
The current study presents an account of mathematics and science knowledgebase of private Gaborone preschool teachers and assesses its influence on their classroom teaching. It assesses their Subject Matter Knowledge (SMK) and Pedagogical Content Knowledge (PCK) and scales their views on the Best Practices for mathematics and science teaching in preschools. A pragmatic paradigm with a concurrent mixed-method mode was used to conduct this study. Using a random-purposive sampling procedure, 64 preschool teachers were selected. Questionnaire and focus group discussions were used for data collection. The quantitative data was analysed using descriptive analysis and presented with the help of frequency Tables and Graphs. The qualitative data was coded and synthesised to receive meaningful information. The findings show that 80% of teachers were trained as primary school teachers; only 14% had professional training in Early Childhood Education (ECE). It further revealed that the teachers had SMK; however, were less proficient in PCK which affected their classroom practices, despite having ample material resources. The preschool teachers viewed the establishment of the Science Center/s for young children and strong administrative support as best practices for teaching mathematics and science in preschools.